Motivasi Pendekatan Saintifik melalui Modulasi Pembelajaran al-Qur’an dan Hadis - Saadahtul Wahidah; Muhammad Abdul Halim Sidiq; Mohammad Darwis (STAI Attanwir Bojonegoro, 2022)
Increasing students' learning motivation towards learning the Qur'an and Hadith of course we are required to solve problems that occur in the world of education today. Problems that occur in the student learning module because this module is a form of supporting factor in an effort to increase student learning motivation. The reality in schools for subjects of the Qur'an and Hadith tends to be considered a boring lesson due to the methods used or other factors. From here, the researcher took the initiative to develop a module through a scientific approach to increase student learning motivation. In this study, researchers chose to use qualitative methods through data sources from observations, interviews, intentionally or not, and used descriptive methods in analyzing. Based on the results of the data obtained by the researchers and the analysis that has been carried out, it can be seen that the development of the module through a scientific approach can increase the learning motivation of Mts Nurul Hasan students towards the Qur'anic Hadith subjects. In addition to developing learning modules, the institution must maximize the supporting factors and minimize the inhibiting factors that occur so that the process of increasing student motivation will be maximized